KOMODIFIKASI KEMISKINAN OLEH MEDIA TELEVISI - As’ad Musthofa (Program Studi Ilmu Komunikasi FBIK Unissula, 2012)
The presence of his television special mass media in Indonesia has become an important part in the social life of our society. Television with a wide range of events that the screening had been able to attract viewers. Television not only as a product of the technology per se, but has been transformed into an instrument that enables the widespread distribution of values. We brought in, and often consider the reality of the media as a reality that happens in real life as it represents, as well as reality show. When a reality show with the theme of poverty worked and produced by a production house and television stations, then there is the practice of commodification of poverty. Media have economic interests behind the phenomenon of the proliferation of poverty-themed reality show. How can poverty be a lucrative commodity for the television media industry. Intelligently production house had transformed the lives of people living with poverty being a part of their business, so that anything can be turned into a commodity worth watching alias experience for the commodification and commercialized.Poverty used as a commodity exaggerated or manipulated, added to certain engineering that plot became more melancholy and dramatic so as to public attention. The goal is to get a high rating from the television audience. High rating is commonly embedded in the program, so that the production can keep costs as low as possible and gain as high. The reason for producing program-themed reality show poverty no matter how great the program is able to attract advertisers to advertise their products on the sidelines of the event display. So the production house income benefit greatly from these ads. Thus, we know how a poverty commercialized for the benefit of the television media industry